A Review of Four Health Procedures That School Nurses May Encounter. (January 2018) - Toothaker, Rebecca; Cook, Pamela
The school nurse plays a vital role in providing care and meeting the health needs of students in the school setting. Students attend school with chronic conditions and complex medical problems such as quadriplegia, cerebral palsy, spina bifida, and muscular dystrophy. It is the responsibility of the school nurse to provide appropriate assessment, early intervention, and care for children in the school environment. The purpose of this article is to review and discuss the knowledge and skills the school nurse needs to care for students with central venous lines, gastrostomy tubes, altered urinary elimination, and tracheostomies.